Parental scaffolding and problem-solving skills in early childhood: a systematic literature review - Ismail, Nellie; Dahamat Azam, Mohamad Naqiuddin; Daud, Mohd Najmi; Arshat, Zarinah; Juhari, Rumaya; Madon, Zainal (ACS Publisher, 2024)
Parental scaffolding in socio-cultural contexts was found to promote the development of children’s problem-solving skills. However, there’s been a lack of systematic reviews exploring how parental scaffolding influences problem-solving skills among children during their early years. The current article seeks to examine the existing research on the influence of parental scaffolding on problem-solving skills in early childhood. Following the PRISMA Statement (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) review method, a systematic review of the Scopus and Google Scholar databases identified five relevant studies. A comprehensive analysis of these articles resulted in the identification of two primary themes-verbal instructions and contingent scaffolding. The reviewed studies revealed that early childhood problem-solving skills are much improved when parents use verbal explanations. It seems that employing verbal instructions offers a multimodal approach that is effective for young children, facilitating a better grasp and applying problem-solving techniques. Understanding the influence of parental scaffolding on early childhood problem-solving skills has implications for parenting education programs, early childhood interventions, and the design of family-oriented interventions aimed at optimizing cognitive development during this critical developmental stage.